2016
DOI: 10.1371/journal.pone.0168733
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Recombinase Polymerase Amplification Assay for Rapid Detection of the Mycobacterium avium subsp. paratuberculosis

Abstract: BackgroundThe detection of Mycobacterium avium subsp. paratuberculosis (MAP) infections in ruminants is crucial to control spread among animals and to humans. Cultivation of MAP is seen as the gold standard for detection, although it is very time consuming and labour intensive. In addition, several PCR assays have been developed to detect MAP in around 90 minutes, but these assays required highly sophisticated equipment as well as lengthy and complicated procedure.Methodology/Principal FindingsIn this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Both tests were able to detect ten imp copies per reaction, regardless if the target was present in pure form or mixed with unrelated DNA from healthy plants. This copy number is in the range to those reported for other bacterial pathogens, like Mycobacterium avium , where the detection limit was 50 target molecules (Hansen et al., ). RPA detection limit is also similar to an isothermal LAMP assay developed for the 16SrX group fruit tree phytoplasmas (De Jonghe, De Roo, & Maes, ) or for a generic TaqMan real‐time PCR procedure based on 16S rDNA primers and probe (Christensen et al., ).…”
Section: Discussionmentioning
confidence: 51%
“…Both tests were able to detect ten imp copies per reaction, regardless if the target was present in pure form or mixed with unrelated DNA from healthy plants. This copy number is in the range to those reported for other bacterial pathogens, like Mycobacterium avium , where the detection limit was 50 target molecules (Hansen et al., ). RPA detection limit is also similar to an isothermal LAMP assay developed for the 16SrX group fruit tree phytoplasmas (De Jonghe, De Roo, & Maes, ) or for a generic TaqMan real‐time PCR procedure based on 16S rDNA primers and probe (Christensen et al., ).…”
Section: Discussionmentioning
confidence: 51%
“…Substances present in the sample matrix can interfere with the enzymatic nucleic acid amplification. Previous studies [ [41] , [42] , [43] ] have reported that the presence of background DNA or specific concentration of ions in the sample could have a negative influence on the RPA sensitivity. In our study, the lower limit of detection obtained for YMMV could be explained by the higher levels of polysaccharides contained in extracts obtained from D. alata compared to D. rotundata leaves [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, RPA assays have been established and reported for the rapid detection of several pathogens [ 1 11 18 ]. Moreover, a real-time RPA assay for detecting M. paratuberculosis DNA has also been developed [ 7 ]. However, an RPA-LFD assay for M. paratuberculosis detection has not been established.…”
Section: Introductionmentioning
confidence: 99%